Relationship between selected variables and photosynthetic rates in two aquatic plants - Villegas, Clarita Floreta 1946- (1975)
The purpose of the study is to determine the relationship between the rate of photosynthesis and certain variables such as light intensity, quality of light, carbon dioxide concentration of the medium and temperature on the rate of bubble production as an index of the rate of photosynthesis in Hydrilla and Ceratophyllum. Results of the study show that the effect of the different wavelengths on reactions is not the same for all plants. Some plants have higher photosynthethic rates.
Thesis (M.A.T.)--University of the Philippines, Diliman.
Keywords: Hydrilla; Ceratophyllum; Photosynthesis